1980
DOI: 10.1258/002367780780937454
|View full text |Cite
|
Sign up to set email alerts
|

Stress response of rats to handling and experimental procedures

Abstract: The effects were observed of moving male, adult Han:Sprague rats in their cages or of exposure to ether for 1 min on the plasma concentration profiles of 25 blood characteristics linked with stress and shock reactions. 5 min after the stress serum prolactin, corticosterone, thyroid-stimulating hormone, follicle-stimulating hormone, luteinizing hormone, triiodothyronine and thyroxin levels were elevated 150-500% compared with those in blood collected within 100 s of entering the animal room. Heart rate (teleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
1
2

Year Published

1986
1986
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(109 citation statements)
references
References 27 publications
5
101
1
2
Order By: Relevance
“…Twenty-four hours after surgery, the concentrations began to fluctuate in a daily rhythm with high concentrations in the evening and low concentrations in the morning. A similar pattern has been registered previously by Windle et al (1998a,b), who found values very similar to the ones reported in the present study, which are also in the same range (100 ng/ml) as described by Gärtner et al (1980) in unstressed rats. This rather quick return to normality, even if stress persists, has been previously described by Manser (1992).…”
Section: Discussionsupporting
confidence: 93%
“…Twenty-four hours after surgery, the concentrations began to fluctuate in a daily rhythm with high concentrations in the evening and low concentrations in the morning. A similar pattern has been registered previously by Windle et al (1998a,b), who found values very similar to the ones reported in the present study, which are also in the same range (100 ng/ml) as described by Gärtner et al (1980) in unstressed rats. This rather quick return to normality, even if stress persists, has been previously described by Manser (1992).…”
Section: Discussionsupporting
confidence: 93%
“…These results were in agreement with calculations on substrate oxidation in animals exposed to a similar feeding regime [31] which showed a high level of fat oxidation during periods of restriction, whereas protein oxidation provided the major contribution to the total heat production when the food supply was ample, and with results by Fink and Tauson [17] showing negative values for retained energy [22] showing direct proportionality between insulin and level of food intake, and own previous results in mink [17]. [17], pig [16] and sheep [27] showing that [10], which probably was caused by the handling in connection with blood sampling (mink: B o rsting and Damgaard [ 10] and rat: Gdrtner et al [19]). The differences in glucose were, however, small throughout the experiment, confirming the results of Armstrong and Britt [3] showing that …”
supporting
confidence: 66%
“…To minimize the effect of sampling order on the values of corticosterone and thyroxine (described by Gä rtner et al 1980, Shanks et al 1990, Dahlborn et al 1996, four mice were euthanized together in their home cage and sampling was done alternating in groups of one cage per each group (NE, E1, E2). The sampling order was unalterable until all of the animals had been euthanized.…”
Section: Euthanasiamentioning
confidence: 99%